Global response of underground structures subjected to ground shock with consideration of rise time. Issue 143 (April 2021) - Zhou, Hongyuan; Cong, Pengli; Wang, Xiaojuan; Wang, Yonghui; Dai, Huliang; Yu, Shangjiang; Du, Jianguo
Abstract: The global response of underground structures subjected to ground shock is investigated theoretically, experimentally and numerically. Non-zero rise time of ground shock is taken into account in the theoretical prediction. A scale model field test is conducted to examine the prediction accuracy, suggesting that the conventional method without ground shock rise time may result in over-design, while the present approach with rise time more reasonably predicts the global acceleration response which is the excitation to the affiliated devices inside the structure. Subsequently, shock response spectra of inside devices with mounting are established to evaluate the shock environment within the underground structure. Numerical simulation further complements the study. With combined approach, the key factors influencing the global response and in-structure shock of underground structures are discussed in detail, whose findings facilitate more reasonable design of underground structures in terms of shock environment assessment and mitigation. Highlights: The global response of a ground shock loaded underground structure is formulated considering rise time. A small scale test is conducted to validate the theoretical prediction. Ground shock rise time remarkably affect the shock environment inside the structure.